2006
DOI: 10.1007/bf03194628
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the efficiency of nitrogen utilization and photosynthetic activity of flag leaves among the old and modern germplasm of winter wheat

Abstract: Genotypic variation in major components of the efficiency of nitrogen utilization and photosynthetic activity of flag leaves among old (released 1881-1963) and modern (released 1969-2003) cultivars of winter wheat was studied in field conditions under varied N fertilization levels (110, 90 and 80 kg N ha-1). Significant genotypic differences were observed for all characters. Their heritabilities ranged from 0.37 to 0.93 and were the lowest for the leaf efficiency of gas exchange, photosynthetic rate, straw N c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…4). This supports the results reported by Hubick (1990), Górny and Garczyński (2002), and Hamaoka et al (2013). However, Brueck and Senbayram (2009), who conducted a quantitative analysis of the influence of N supply on tobacco WUE, reported that WUE and DM proportionally increase with increases in N supply.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4). This supports the results reported by Hubick (1990), Górny and Garczyński (2002), and Hamaoka et al (2013). However, Brueck and Senbayram (2009), who conducted a quantitative analysis of the influence of N supply on tobacco WUE, reported that WUE and DM proportionally increase with increases in N supply.…”
Section: Discussionsupporting
confidence: 93%
“…In this case, the reduction in WUE observed in nodulated plants casts doubt on the association with BNF and suggests that it is driven by N excess. The difference in WUE between nodulated plants and non-nodulated plants can only be directly related to N fixation cost when WUE has no relationship with the internal N conditions of plants (Hubick, 1990;Górny andGarczyński, 2002; Hamaoka et al, 2013). There is an optimum curvilinear relationship between 【Short Report】 plant growth rates and N concentration in culture medium (Hozumi et al, 1960); plant growth rates are reduced under either conditions of N shortage or N excess.…”
mentioning
confidence: 99%
“…Although numerous reports on genotypic variation in components of N efficiency already suggest potential applications of this genetic knowledge for wheat improvements (Ortiz-Monasterio et al, 1997;El Bassam, 1998;Le Gouis et al, 2000;Gorny et al, 2006;Kichey et al, 2007;Baresel et al, 2008;Barraclough et al, 2010), relatively fewer attempts have been made to breed wheat for these traits (Van Ginkel et al, 2001;Wolfe et al, 2008). Progress in breeding bread wheat better adapted to less favorable nitrogen fertilization is still restricted for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Different morphophysiological characteristics, associated with both the uptake capacity (NUpE; defined here as a proportion of total N uptake to N availability in the soil) and efficiency of nitrogen utilization in grain mass formation (NUtE; defined here as the grain mass formed per unit of N absorbed), appear to be critical components of NUE (Moll et al 1982;Huggins and Pan 2003). Although numerous reports on genotypic variation in components of N efficiency already suggest potential applications of this genetic knowledge for wheat improvements (Dhugga and Waines 1989;Le Gouis and Pluchard 1996;Ortiz-Monasterio et al 1997;El Bassam 1998;Le Gouis et al 2000;Oracka et al 2000;Górny et al 2006a;Laperche et al 2006a;Kichey et al 2007;Baresel et al 2008;Barraclough et al 2010), relatively fewer attempts have been made to breed wheat for these traits (Van Ginkel et al 2001;Brancourt-Hulmel et al 2005;Löschenberger et al 2008;Wolfe et al 2008).…”
Section: Introductionmentioning
confidence: 99%